Groupwork activities for improving students-students interaction in the english class at Medalla Milagrosa Middle School, 2016 - Espinosa, Fernando (UDELAS, 2016)
The interaction is an importan step in the development of a class, and it also focuses learning and evolution of a student, so it will be the trend of his investigation at Medalla Milagrosa high school.